Perception of UiTM academic staff toward online transaction / Faradila Fadil, Mohd Taufiq Saini and Nurhidayah Sahbudin - Fadil, Faradila; Saini, Mohd Taufiq; Sahbudin, Nurhidayah (2012)
According to dictionary definition Online Transaction Processing or also known as OLTP can be defined as a computer system where time-sensitive, transaction-related data is processed immediately and is always kept current. Online transaction consists of the buying and selling of products or services over electronic systems such as e-commerce, e-shopping, and many more. Electronic banking or also known as electronic funds transfer (EFT) is simply the use of electronic means to transfer funds directly from one account to another, rather than by check or cash. We can use electronic funds transfer to have our paycheck deposited directly into our bank or credit union checking account, withdraw money from our checking account from an ATM machine with a personal identification number (PIN), at our convenience, day or night. Instruct our bank or credit union to automatically pay certain monthly bills from our account, such as our car loan or our mortgage payment and many more. Electronic commerce often is referred to as ecommerce where the phrase is used to describe business that is conducted over the Internet using any of the applications that rely on the Internet, such as e-mail, instant messaging, shopping carts, Web services, and many more among others (Kalakota and Whinston). Electronic commerce can be between two businesses transmitting funds, goods, services or data or between a business and a customer (Stower 2001). Electronic shopping or e-shopping is the process of selecting, ordering, and paying for goods or services over an electronic network such as the Internet (Hyun-hwa Lee,Jihyun Kim and Ann Marie Fiore).